Co-occurrence of Rapid Gene Gain and Loss in an Interhospital Outbreak of Carbapenem-Resistant Hypervirulent ST11-K64 Klebsiella pneumoniae - Zhang, XiaoTuan; Ouyang, JingLin; He, WenWen; Zeng, Tong; Liu, Bin; Jiang, Hongtao; Zhang, Yunsheng; Zhou, Linlin; Zhou, Haijian; Liu, Zhuoran; Liu, Logen (Frontiers in Microbiology, 2020)
We report an outbreak of carbapenemase-producing, hypervirulent Klebsiella pneumoniae in two hospitals that undergo frequent patient transfers. Analysis of 11 complete assembled genomes showed that the bacteria were ST11-K64 strains. Moreover, 12 single nucleotide polymorphisms (SNPs) identified the strains as having originated from the same cluster, and were also indicative of interhospital transmission of infection. Five plasmids were assembled in each of the strains. One plasmid carried several virulence genes, including the capsular polysaccharide regulators rmpA and rmpA2. Two others carried antimicrobial-resistance genes, including one for carbapenem resistance, blaKPC2. Comparative genomic analysis indicated the occurrence of frequent and rapid gain and loss of genomic content along transmissions and the co-existence of progeny strains in the same ward. A 10-kbp fragment harboring antimicrobial resistance-conferring genes flanked by insert sequences was missing in a plasmid from strain KP20194c in patient 3, and this strain also likely subsequently infected patient 4. However, strains containing the 10-kbp fragment were also isolated from the ward environment at approximately the same time, and harbored different chromosome indels. Tn1721- and multiple additional insert sequence-mediated transpositions were also seen. These results indicated that there is a rapid reshaping and diversification of the genomic pool of K. pneumoniae facilitated by mobile genetic elements, even a short time after outbreak onset. ST11-K64 CR-hvKP strains have the potential to become new significant superbugs and a threat to public health.